Experiences of Post-Colonial Women in Grassroots Organizations in Mali: The Case of “L’Association des Femmes Fabricantes de Savon, Koulikoro Plateau I” (AFFSKP), Mali - Maimouna Konate (Adult Education Research Conference, 2007)
This qualitative research conducted in Mali during June-August 2006 explored the perceptions of thirty-eight women of a grassroots organization named “Les Femmes Fabricantes de Savon de Koulikoro Plateau I.” This study examined the experiences of poor women in Mali and sought to include their voices as they told their stories.